Flow Through Isotropic Granular (Non Consolidated) Porous Media (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
A generalization of the Navier-Stokes equations, proposed by Prieur du Plessis and Masliyah to model laminar flow through a rigid isotropic granular (non consolidated) porous medium of spatially varying permeability, is analyzed. Results concerning existence and regularity of solutions, similar to the ones holding the classical Navier-Stokes equations, are proved.